Implementation of Islamic Economic Law in Strengthening Sharia-Based Economic Systems - Suprianik (ILAW, 2025)
This study analyzes the implementation of Islamic economic law in strengthening sharia-based economic systems. The research aims to examine how Islamic legal principles are applied in modern financial practices and how they contribute to building ethical, fair, and sustainable economic systems. A normative legal research method is used with statutory and conceptual approaches, relying on secondary data from legal documents, academic literature, and institutional reports. The findings show that Islamic economic law plays a crucial role in promoting justice, financial inclusion, and risk-sharing mechanisms through institutions such as Islamic banking, zakat, and waqf systems. However, challenges such as regulatory differences, limited human resources, and lack of public understanding still hinder its optimal implementation. The study concludes that strengthening Islamic economic law requires regulatory harmonization, institutional development, and increased public awareness to ensure the sustainability of sharia-based economic systems.